Kenya : Fifth Review Under the Three-Year Arrangement Under the Extended Credit Facility and Request for a Waiver and Modification of Performance Criteria-Staff Report; Staff Supplement; and Press Release. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2013)
Economic activity in Kenya has remained resilient to uncertainty surrounding the elections, the impact of the European crisis, and security-related concerns. Fiscal policy is in line with the program despite difficulties. International reserves are on the rise, and the deficit of the external current account has shrunk significantly. Key structural reforms to strengthen the institutional framework are under way. A peaceful political transition, strengthened macroeconomic conditions, and structural reforms could unleash Kenya's growth potential, attract foreign investment, and lay the basis for transforming the country into an emerging-market economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet